TIGIT immunosuppressive role in female reproductive system malignant neoplasms: from mechanism to therapy - A. U. Khamadyanova; A. I. Romanova; A. N. Sklyar; A. P. Yamilova; M. G. Miranda Planas; G. D. Galeeva; S. R. Khakimov; A. A. Yakubov; S. K. Bikinyaev; Sh. M. Mammaev; A. A. Vardanyan; P. A. Kantaeva; et al. (Акушерство, гинекология и репродукция)
Introduction. Malignant neoplasms of the female reproductive system (ovarian, endometrial, and cervical cancers) account for a significant proportion of female oncology morbidity and mortality. Standard treatment methods, including surgery, chemotherapy, and radiotherapy, show limited efficacy in recurrent and drug-resistant tumors. The development of immunotherapy, particularly immune checkpoint inhibitors (ICI), has opened new therapeutic avenues; however, their clinical effectiveness in gynecologic oncology remains suboptimal. In connection with this, it has increased an interest in novel targets, notably TIGIT (T-cell immunoglobulin and ITIM domain), a co-inhibitory receptor expressed on T-cells and natural killer cells (NK-cells), which plays a key role in establishing an immunosuppressive tumor microenvironment.Aim: to systematize current data on the biological function of TIGIT and relevant ligands, its role in immunosuppression in malignant neoplasms of the female reproductive system as well as evaluate a therapeutic potential of its blockade during a personalized immunotherapy.Materials and Methods. This review was conducted according to the PRISMA methodology. There was performed a systematic literature search for publications from 2013 to 2024 in the databases PubMed/MEDLINE, Scopus, Web of Science, Embase, Google Scholar, and ClinicalTrials.gov. A total of 91 scientific sources and 7 registered clinical trials were included. Original studies, meta-analyses, reviews, guidelines, and clinical trial reports were analyzed.Results. TIGIT interacts with several ligands (CD155, CD112, Nectin-4, Fap2), leading to suppression of NK-cells and CD8+ T-cells activity, macrophage polarization toward M2 phenotype, activation of regulatory T-cells (Treg), and impaired antigen presentation. TIGIT is co-expressed with PD-1 (programmed cell death protein 1) and CD96, forming a suppressive signaling network. Its elevated expression is associated with disease progression in ovarian, endometrial, and cervical cancers, reduced cytotoxicity of tumor-infiltrating lymphocytes (TIL), and poor prognosis. TIGIT blockade, especially in combination with PD-1/PD-L1 (programmed cell death ligand 1), restores effector cell function and enhances antitumor immunity in preclinical and clinical studies.Conclusion. TIGIT is a promising immunotherapeutic target in malignant neoplasms of the female reproductive system. Its blockade may improve treatment outcomes in patients with recurrent and resistant cancert ypes. Combined approaches involving anti-TIGIT agents require further clinical validation but even today they offer new directions in targeted therapy and personalized management in gynecologic oncology.